SIGNIFICANCE OF INCOME GENERATION ACTIVITIES UNDER MICRO-FINANCE:A STUDY OF MICRO-FINANCE GROUPS IN WAYANAND DISTRICT, KERALA - Emil Mathew (INSTITUTE FOR SOCIAL AND ECONOMIC CHANGE, 2005)
The present paper discusses the necessity of promoting income-generating activities (IGAs) under micro-finance programmes. Under micro-finance programmes, the principle of joint liability ensures access to credit. In the absence of remunerative IGAs, peer pressure forces the members to borrow loans from various sources at the time of repayment and results in indebtedness. The present paper examines the factors influencing the members to undertake IGAs and puts forth some policies to promote productive activities.